An ISM analysis of the critical success factors in ERP implementation - Hankin, Paul; Almanei, Mohammed; Salonitis, Konstantinos (IOS, 2021)
Enterprise Resource Planning (ERP) offers many benefits in aligning business operations. However, these implementations can be problematic and prone to failure. Critical success factors (CSF) which can improve the success rates of implementation have been researched and an interpretive structural modelling (ISM) was conducted to identify the interrelationships between factors. An ISM based model was created and this was achieved by completing the self-interaction matrix (SSIM), reachability matrix and level partitioning. This led to an ISM-based model being created followed by a cross-impact matrix multiplication (MICMAC) analysis to identify the factor’s relative driving power and level of dependence. The project revealed that top management support was the strongest CSF with a high driving power and low dependence. In addition, fourteen other factors displayed strong driving power with high dependence. The findings from the project were summarized into a recommended framework for manufacturing organizations to follow to increase the likelihood of a successful ERP implementation.
Keywords: MICMAC; ISM; ERP systems; Enterprise resource planning